Heavy metal sources and ecological risk assessment of typical lead-zinc mining areas in Hebei Province - An LIU; Congling YU; Liping WANG; Juanjuan SONG; Lianwei SUN; Qian JIN; Menghua SUN (地质科技通报, 2024)
Objective To reveal the sources and ecological risks of heavy metals in a typical lead-zinc mining area in Hebei Province, 156 soil samples were collected around a zinc mining area in Hebei Province through a systematic field sampling method. Methods The sources of heavy metals in the area were analysed via principal component analysis(PCA) and a positive matrix factorization(PMF) model. The risk assessment was carried out according to the index of geoaccumulation method and potential ecological risk index method. Results The results show that the mean values of Cr, Ni, Cu, Zn, As, Cd, Pb and Hg are 53.6, 25.7, 62.7, 692, 10.6, 1.75, 142, 0.129 mg/kg, respectively. Except for Cr, Ni and As, the other 5 elements present at different pollution levels. Above the background values of the soils in Hebei Province, the coefficient of variation of Hg, Cd, Zn, Pb and Cu is more than 1.75, and the coefficient of variation of As exceeds 0.5, indicating the high variability of these 6 elements. The results of the source analysis reveal that the main sources of soil heavy metals include mining activities, natural sources, agricultural activities, and gold smelting. Zn, Cd and Pb were mainly derived from mining activities; Cr and Ni were influenced by natural parent materials and were derived from natural sources; Cu was mainly derived from agricultural activities and mining activities; As was controlled by natural sources, mining activities and agricultural activities; and Hg was originated from mainly gold smelting and mining activities. The combination of PCA and the PMF model to corroborate each other facilitates the reliability of the heavy metal source analysis results. Conclusion There is anthropogenic Hg and Cd contamination in this area, as indicated by the high geoaccumulation indices and potential ecological risk indices. In addition, the ecological risk in general was found to be very high, and attention needs to be given to and management work to be carried out.